A batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers
Through the batch non-melting treatment method of silicon-doped boron-nitrogen precursor fibers, melt spinning, multi-stage composite treatment and post-treatment technology, the existing boron nitride-based fibers have been solved, and efficient and uniform non-melting treatment is achieved, providing a foundation for the preparation of high-performance boron nitride-based ceramic fibers.
Patent Information
- Application Number
- CN202411686603.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing non-melt treatment methods for boron nitride-based fibers have problems such as introducing heterogeneous elements, high processing cost, poor non-melt treatment effect and low processing efficiency, making it difficult to achieve a high degree of boron nitride-based fibers with a low softening point, and a uniform non-melt batch processing.
The batch non-melting treatment method of silicon-doped boron-nitrogen precursor fiber is adopted. By melt spinning, multi-stage composite treatment and post-treatment under nitrogen protection, including electron beam irradiation and atmosphere heat crosslinking, the fiber is achieved with a high degree and uniform non-melting.
This method effectively avoids the uneven degree of melting, degradation and crosslinking of fibers, improves the non-melting treatment efficiency and effect, reduces the treatment cost, and realizes the high-degree, uniform and non-melting batch processing of boron nitride-based fibers at low softening point, laying the foundation for the subsequent preparation of high-performance boron nitride-based ceramic fibers.
Smart Images

Figure CN119162685B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of boron nitride-based fibers, and in particular to a batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers. Background Art
[0002] Boron nitride (BN) fiber, as a material with low dielectric loss, has been widely studied for its application in wave-transmitting radomes alone or in combination with other ceramic materials. In addition, due to its good high-temperature stability and low high-temperature ablation rate, it has great application prospects in the aerospace field. However, due to the generation of micro-defects in the pyrolysis process of single-phase boron nitride, its oxygen resistance and water erosion resistance are poor in high-temperature environments. In response to this defect, many studies on silicon-boron-oxygen nitride fibers based on BN have been carried out. At present, the main boron nitride-based fibers include BN, BNO, SiBN, SiBON, etc.
[0003] In the prior art, the main method for preparing this type of nitride fiber is the polymer precursor conversion method in the organic method, which is specifically: first synthesize a spinning-grade polymer precursor, and then obtain boron nitride-based ceramic fibers through spinning, infusibility treatment and high-temperature sintering. Among them, the infusibility treatment is to cause the precursor fiber to undergo an intermolecular cross-linking reaction, increase the molecular weight, and increase the melting point to no longer melt, so that the precursor fiber maintains the fiber shape during the subsequent high-temperature sintering process, avoiding the occurrence of melt and yarn, which leads to a decrease in fiber strength. At the same time, the infusibility treatment can also increase the yield of ceramic fibers, reduce ceramic fiber defects, and improve the strength of ceramic fibers.
[0004] At present, the common infusibility treatment methods for precursor fibers mainly include chemical atmosphere infusibility method, thermal crosslinking infusibility method and electron beam irradiation infusibility method. Among them, the thermal crosslinking infusibility method is that at a certain temperature, the fiber undergoes a self-crosslinking reaction by its own active groups to achieve infusibility; the advantage of this method is that no foreign elements are introduced during the infusibility process, but the infusibility treatment takes a long time and has a high processing cost, and excessive heat release during the reaction process can easily lead to fiber melting and spinning or thermal degradation. The chemical atmosphere infusibility method uses the active atmosphere required for crosslinking to react with the fiber in a gas-solid reaction; however, foreign elements will be introduced during the infusibility process, which will lead to fiber pore defects or difficulty in oxygen element escape, etc.; and when the fiber collection amount is large or the fiber diameter is large, it is difficult to achieve the ideal infusibility effect in a short period of time through atmosphere infusibility crosslinking, and there is a problem of uneven crosslinking degree between the inner and outer layers of the fiber. The electron beam irradiation infusibility method is to trigger the crosslinking of precursor fibers through the energy of high-energy particles (such as gamma rays, etc.), connect the polymer chains together through the radiation effect, thereby increasing the molecular weight, and finally forming a network polymer to achieve infusible crosslinking; the prior art discloses that under the protection of nitrogen or inert gas, the original fibers are irradiated under an electron beam to obtain electron beam irradiation crosslinked boron nitride-based infusible fibers; since the heat released during the crosslinking process is relatively small, the obtained infusible fibers do not show the phenomenon of stranding; however, the electron beam irradiation time required for this method is long (the overall infusibility treatment time is about 3 hours), and there is a problem of radiation degradation during the irradiation crosslinking process, that is, the irradiation dose or dose rate is too large, resulting in the breakage of the polymer main chain and the reduction of the molecular weight, which ultimately leads to the reduction of fiber performance after treatment.
[0005] Furthermore, in the existing infusibility treatment of boron nitride-based ceramic fibers, it is impossible to achieve high-degree and uniform infusibility batch treatment of low softening point boron nitride-based original fibers while taking into account both the infusibility treatment efficiency and the infusibility treatment effect. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a batch infusible treatment method for silicon-doped boron nitride precursor fibers, which can overcome the problems of the existing infusible treatment methods that may introduce foreign elements, have high treatment costs, poor infusible treatment effects and low treatment efficiency; effectively avoid the melting and twisting, degradation and uneven cross-linking of the fibers during the infusible treatment process, and can achieve high-degree and uniform infusibility batch treatment of low-softening-point boron nitride-based fibrils while taking into account both the infusible treatment efficiency and the infusible treatment effect, thereby effectively reducing the treatment cost.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] A batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers comprises the following steps: melt spinning, multi-stage composite treatment, and post-treatment.
[0009] The melt spinning method is to use polysilicon borazane as an organic precursor raw material for melt spinning under nitrogen protection to obtain BN-based fibrils.
[0010] Preferably, the BN-based fibrils are continuous fibers with smooth and dense surfaces and a diameter of 12-15 μm.
[0011] Preferably, the spinning viscosity of polysilicon borazane is 250-850 Pa·s, the molecular weight is 550-1500, and the silicon content is 5-20wt%.
[0012] The multi-stage composite treatment method is to place the BN-based original fiber obtained in the melt spinning step in an electron beam constant temperature irradiation device under the protection of inert gas, replace the inert gas in the electron beam constant temperature irradiation device with a mixed treatment gas for 3 times, and then heat the mixture at 3-6 m / s. 3 The mixed treatment gas is continuously introduced at a rate of 1000 Å / h, the irradiation energy is controlled to be 2-2.5 MeV, and the first-level irradiation treatment, the second-level irradiation treatment, the third-level irradiation treatment, and the fourth-level irradiation treatment are continuously performed to obtain a multi-level composite treated fiber.
[0013] Furthermore, the mixed processing gas is a mixed gas of ammonia and inert gas nitrogen; preferably, the volume ratio of ammonia to nitrogen in the mixed processing gas is 1:2-5; preferably, the flow ratio of ammonia to nitrogen in the mixed processing gas is 1:2-5.
[0014] Furthermore, in the primary irradiation treatment, in a mixed treatment gas environment, the beam current is controlled to be 1.8-2.4 mA, the irradiation temperature is 20-40° C., and the irradiation treatment is performed for 10-30 minutes to complete the primary irradiation treatment.
[0015] Furthermore, in the secondary irradiation treatment, in the mixed treatment gas environment, the beam current is adjusted to 4-6mA, the irradiation temperature is 45-60°C, and after irradiation treatment for 5-30 minutes, the introduction of the mixed treatment gas is stopped, and the mixed treatment gas in the electron beam constant temperature irradiation device is completely replaced by inert gas, and then kept at 45-60°C for 10-30 minutes to complete the secondary irradiation treatment.
[0016] Furthermore, in the third-level irradiation treatment, in an inert gas environment, the beam current is adjusted to 8-10 mA, the irradiation temperature is 65-110° C., and the irradiation treatment is performed for 5-25 minutes to complete the third-level irradiation treatment.
[0017] Furthermore, in the fourth-level irradiation treatment, in an inert gas environment, the beam current is adjusted to 12-14 mA, the irradiation temperature is 120-160° C., the irradiation treatment is performed for 5-15 minutes, and the irradiation is stopped to complete the fourth-level irradiation treatment.
[0018] The post-treatment method is to transfer the multi-stage composite treated fibers into a heating furnace for annealing to obtain infusible fibers.
[0019] Preferably, the annealing temperature is 280-300° C., and the annealing time is 20-60 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The batch infusible treatment method of silicon-doped boron nitrogen precursor fibers of the present invention comprises the following steps: first, polysilicon borazane is used as a raw material for melt spinning to obtain BN-based fibrils, and then the active atmosphere during electron beam irradiation is controlled to perform multi-stage composite treatment on the BN-based fibrils, and an electron accelerator is used to promote crosslinking between molecules in the BN-based fibrils, thereby improving the uniformity of the infusible fibers; at the same time, on the basis of electron beam crosslinking, atmosphere heat crosslinking is also combined, and the radiation heat is effectively used to promote the active groups in the BN-based fibrils to further undergo transamination reaction, thereby promoting the infusible fibers to achieve a higher degree of crosslinking, and effectively reducing the required irradiation dose and treatment time, thereby further improving the uniformity of the infusible fibers. The uniformity of highly infusible fibers provides an infusible treatment effect, improves production efficiency, reduces production costs, and reduces environmental pollution; the aforementioned technical means cooperate with each other and work synergistically to effectively overcome the problems of existing infusible treatment methods that may introduce foreign elements, high treatment costs, poor infusible treatment effects, and low treatment efficiency; effectively avoid the melting and twisting, degradation, and uneven cross-linking of fibers during the infusible treatment process, and can achieve high-degree, uniform infusibility batch processing of low softening point boron nitride-based fibrils while taking into account both the infusible treatment efficiency and the infusible treatment effect, laying the foundation for the subsequent preparation of high-performance boron nitride-based ceramic fibers.
[0022] (2) Compared with the existing infusibility treatment method, the batch infusibility treatment method of silicon-doped boron nitrogen precursor fibers of the present invention has a higher dosage rate per unit time, and the treatment time required for the infusibility treatment is shorter (no more than 2 hours). Moreover, the fibers treated by the method of the present invention have a higher degree of infusibility. In the subsequent preparation process of high-performance boron nitride-based ceramic fibers, the ammonia heat treatment rate is faster, and the entire heat treatment cycle of the high-performance boron nitride-based ceramic fibers can be shortened to less than 10 hours.
[0023] (3) The infusible temperature of the obtained infusible fibers by the batch infusible treatment method of the silicon-doped boron nitrogen precursor fibers of the present invention is not lower than 500°C, and the fiber surface is smooth and dense, without melting and twisting. The weight loss rate of the infusible fibers in a nitrogen environment at 1000°C does not exceed 17.9%; the gel content of the infusible fibers can reach 98.6%.
[0024] (4) The infusible fibers prepared by the batch infusible treatment method of the silicon-doped boron nitrogen precursor fiber of the present invention can achieve high-degree and uniform infusible batch treatment of low softening point boron nitride-based original fibers while taking into account the infusible treatment efficiency and infusible treatment effect, laying a foundation for the subsequent preparation of high-performance boron nitride-based ceramic fibers; the silicon-doped boron nitrogen fiber prepared by the method has a smooth surface, no foreign element dissolution pore defects, and a tensile strength of up to 1.27GPa and an elastic modulus of up to 103GPa. After the silicon-doped boron nitrogen fiber is placed in 100°C boiling water for 3 hours, the tensile strength retention rate can reach 98.9%; after the silicon-doped boron nitrogen fiber is placed in an oxygen-nitrogen mixed gas environment (the volume ratio of oxygen to nitrogen is 3:97) and heat-treated at 1400°C for 30 minutes, the tensile strength retention rate can reach 95.7%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the infusible fiber prepared by the infusible treatment method of Example 1.
[0026] Figure 2 The thermogravimetric TG curves of the infusible fibers prepared by the infusible treatment method of Example 1, and the infusible fibers of Comparative Examples 1 and 2 in a nitrogen environment are shown respectively; in the figure, curve a is the TG curve of Comparative Example 1 (whose thermal weight loss is 11.5%), curve b is the TG curve of Example 1 (whose thermal weight loss is 17.9%), and curve c is the TG curve of Comparative Example 2 (whose thermal weight loss is 44.2%).
[0027] Figure 3 This is a SEM image of the infusible fiber prepared by the infusible treatment method of Comparative Example 2. DETAILED DESCRIPTION
[0028] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0029] Example 1
[0030] This embodiment provides a batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers, specifically:
[0031] 1. Melt spinning
[0032] Under nitrogen protection, polysilicon borazane is used as an organic precursor raw material for melt spinning to obtain BN-based fibrils; the BN-based fibrils are continuous fibers with a smooth and dense surface and a diameter of 12 μm.
[0033] Among them, the spinning viscosity of polysilicon borazane is 600 Pa·s, the molecular weight is 1050, and the silicon content in polysilicon borazane accounts for 17wt%.
[0034] 2. Multi-level composite processing
[0035] Under the protection of inert gas (nitrogen), the BN-based original fibers obtained in the melt spinning step were placed in an electron beam constant temperature irradiation device. After the inert gas in the electron beam constant temperature irradiation device was replaced three times with a mixed treatment gas, the inert gas was heated at 4.5 m / s. 3 The mixed treatment gas is continuously introduced at a rate of 1.25 Å / h, the irradiation energy is controlled to be 2.0 MeV, and the first-level irradiation treatment, the second-level irradiation treatment, the third-level irradiation treatment, and the fourth-level irradiation treatment are continuously performed to obtain a multi-level composite treated fiber.
[0036] The mixed processing gas is a mixed gas of active gas (ammonia) and inert gas (nitrogen); the volume ratio of ammonia to nitrogen in the mixed processing gas is 1:5; and the flow ratio of ammonia to nitrogen in the mixed processing gas is 1:5.
[0037] In the primary irradiation treatment, in a mixed treatment gas environment, the beam current was controlled to be 2.4 mA, the irradiation temperature was 28° C., and the irradiation treatment was performed for 30 minutes to complete the primary irradiation treatment.
[0038] In the secondary irradiation treatment, in the mixed treatment gas environment, the beam current was adjusted to 5.2 mA and the irradiation temperature was 55°C. After irradiation treatment for 20 minutes, the introduction of the mixed treatment gas was stopped, and the mixed treatment gas in the electron beam constant temperature irradiation device was completely replaced by inert gas (nitrogen). The mixed treatment gas was kept at 55°C for 20 minutes to complete the secondary irradiation treatment.
[0039] In the three-level irradiation treatment, in an inert gas (nitrogen) environment, the beam current was adjusted to 9.6 mA, the irradiation temperature was 110°C, and the irradiation treatment was carried out for 15 minutes to complete the three-level irradiation treatment.
[0040] In the fourth-level irradiation treatment, in an inert gas (nitrogen) environment, the beam current is adjusted to 14 mA, the irradiation temperature is 140°C, the irradiation treatment is carried out for 5 minutes, and the irradiation is stopped to complete the fourth-level irradiation treatment.
[0041] 3. Post-processing
[0042] The multi-stage composite treated fibers were transferred into a heating furnace, heated to 300°C, and annealed for 30 minutes to obtain infusible fibers.
[0043] After testing, the infusible fiber obtained by the infusible treatment method of this embodiment has an infusibility temperature of not less than 500°C, and the fiber surface is smooth and dense, and no melting and twisting occurs (such as Figure 1 The weight loss rate at 1000℃ in nitrogen environment is 17.9% (as shown in Figure 2 As shown); the gel content of the infusible fiber is 98.6%. Furthermore, in the infusible treatment method of this embodiment, the infusible treatment (i.e., multi-stage composite treatment) lasts for 1.5 hours, which can improve the infusible treatment efficiency while taking into account the infusible treatment efficiency and infusible treatment effect, and realize the high degree and uniform infusibility of low softening point boron nitride-based fibrils in batches.
[0044] Furthermore, in order to verify the treatment effect of the aforementioned infusible treatment method of this embodiment on boron nitride-based fibers, the infusible fibers obtained by the infusible treatment method of this embodiment were placed in a nitrogen atmosphere, and the heating rate was controlled to be 3°C / min. The temperature was raised to 1000°C and kept warm for 3 hours. Then, in a nitrogen atmosphere, the heating rate was controlled to be 5°C / min, and the temperature was continued to be raised to 1500°C. The temperature was kept warm for 1 hour to obtain silicon-doped boron nitrogen fibers.
[0045] After testing, the final silicon-doped boron nitrogen fiber has a smooth surface, no foreign element dissolution pore defects, a tensile strength of 1.27GPa, and an elastic modulus of 103GPa. After the silicon-doped boron nitrogen fiber was placed in 100°C boiling water for 3 hours, the tensile strength retention rate was 98.9%; after the silicon-doped boron nitrogen fiber was placed in an oxygen-nitrogen mixed gas environment (the volume ratio of oxygen to nitrogen was 3:97) and heat-treated at 1400°C for 30 minutes, the tensile strength retention rate was 95.7%.
[0046] Example 2
[0047] This embodiment provides a batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers, specifically:
[0048] 1. Melt spinning
[0049] Under nitrogen protection, polysilicon borazane is used as an organic precursor raw material for melt spinning to obtain BN-based fibrils; the BN-based fibrils are continuous fibers with a smooth and dense surface and a diameter of 12 μm.
[0050] Among them, the spinning viscosity of polysilicon borazane is 600 Pa·s, the molecular weight is 1050, and the silicon content in polysilicon borazane accounts for 17wt%.
[0051] 2. Multi-level composite processing
[0052] Under the protection of inert gas (nitrogen), the BN-based original fibers obtained in the melt spinning step were placed in an electron beam constant temperature irradiation device. After the inert gas in the electron beam constant temperature irradiation device was replaced three times with a mixed treatment gas, the inert gas was heated at 3 m / s. 3 The mixed treatment gas is continuously introduced at a rate of 1000 rpm / h, the irradiation energy is controlled to be 2.2 MeV, and the first-level irradiation treatment, the second-level irradiation treatment, the third-level irradiation treatment, and the fourth-level irradiation treatment are continuously performed to obtain a multi-level composite treated fiber.
[0053] The mixed processing gas is a mixed gas of active gas (ammonia) and inert gas (nitrogen); the volume ratio of ammonia to nitrogen in the mixed processing gas is 1:3; and the flow ratio of ammonia to nitrogen in the mixed processing gas is 1:3.
[0054] In the primary irradiation treatment, in a mixed treatment gas environment, the beam current is controlled to be 1.8 mA, the irradiation temperature is 25° C., and the irradiation treatment is performed for 25 minutes to complete the primary irradiation treatment.
[0055] In the secondary irradiation treatment, in the mixed treatment gas environment, the beam current was adjusted to 4.5 mA and the irradiation temperature was 50°C. After irradiation treatment for 25 minutes, the introduction of the mixed treatment gas was stopped, and the mixed treatment gas in the electron beam constant temperature irradiation device was completely replaced by inert gas (nitrogen). The mixed treatment gas was kept at 50°C for 15 minutes to complete the secondary irradiation treatment.
[0056] In the three-level irradiation treatment, in an inert gas (nitrogen) environment, the beam current was adjusted to 8 mA, the irradiation temperature was 90°C, and the irradiation treatment was carried out for 10 minutes to complete the three-level irradiation treatment.
[0057] In the fourth-level irradiation treatment, in an inert gas (nitrogen) environment, the beam current is adjusted to 12 mA, the irradiation temperature is 120°C, the irradiation treatment is carried out for 10 minutes, and the irradiation is stopped to complete the fourth-level irradiation treatment.
[0058] 3. Post-processing
[0059] The multi-stage composite treated fibers were transferred into a heating furnace, heated to 290° C., and subjected to annealing treatment at the temperature for 25 minutes to obtain infusible fibers.
[0060] After testing, the infusible fiber obtained by the infusible treatment method of this embodiment has an infusibility temperature of not less than 500°C, and the fiber surface is smooth and dense, and no melting and twisting occurs (such as Figure 1 The weight loss rate at 1000℃ in nitrogen environment is 17.5% (as shown in Figure 2As shown); the gel content of the infusible fiber is 98.2%. Furthermore, in the infusible treatment method of this embodiment, the infusible treatment (i.e., multi-stage composite treatment) takes about 1.5 hours, which can improve the infusible treatment efficiency while taking into account the infusible treatment efficiency and infusible treatment effect, and realize the high degree and uniform infusibility of low softening point boron nitride-based fibrils in batches.
[0061] Furthermore, in order to verify the treatment effect of the aforementioned infusible treatment method of this embodiment on boron nitride-based fibers, the infusible fibers obtained by the infusible treatment method of this embodiment were placed in a nitrogen atmosphere, and the heating rate was controlled to be 3°C / min. The temperature was raised to 1000°C and kept warm for 3 hours. Then, in a nitrogen atmosphere, the heating rate was controlled to be 5°C / min, and the temperature was continued to be raised to 1500°C. The temperature was kept warm for 1 hour to obtain silicon-doped boron nitrogen fibers.
[0062] After testing, the final silicon-doped boron nitrogen fiber has a smooth surface, no foreign element dissolution pore defects, a tensile strength of 1.24GPa, and an elastic modulus of 102GPa. After the silicon-doped boron nitrogen fiber was placed in 100°C boiling water for 3 hours, the tensile strength retention rate was 98.7%; after the silicon-doped boron nitrogen fiber was placed in an oxygen-nitrogen mixed gas environment (the volume ratio of oxygen to nitrogen was 3:97) and heat-treated at 1400°C for 30 minutes, the tensile strength retention rate was 95.4%.
[0063] Example 3
[0064] This embodiment provides a batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers, specifically:
[0065] 1. Melt spinning
[0066] Under nitrogen protection, polysilicon borazane is used as an organic precursor raw material for melt spinning to obtain BN-based fibrils; the BN-based fibrils are continuous fibers with a smooth and dense surface and a diameter of 12 μm.
[0067] Among them, the spinning viscosity of polysilicon borazane is 600 Pa·s, the molecular weight is 1050, and the silicon content in polysilicon borazane accounts for 17wt%.
[0068] 2. Multi-level composite processing
[0069] Under the protection of inert gas (nitrogen), the BN-based original fibers obtained in the melt spinning step were placed in an electron beam constant temperature irradiation device. After the inert gas in the electron beam constant temperature irradiation device was replaced three times with a mixed treatment gas, the inert gas was heated at 6 m 3The mixed treatment gas is continuously introduced at a rate of 1000 Å / h, the irradiation energy is controlled to be 2.5 MeV, and the first-level irradiation treatment, the second-level irradiation treatment, the third-level irradiation treatment, and the fourth-level irradiation treatment are continuously performed to obtain a multi-level composite treated fiber.
[0070] The mixed processing gas is a mixed gas of active gas (ammonia) and inert gas (nitrogen); the volume ratio of ammonia to nitrogen in the mixed processing gas is 1:4; and the flow ratio of ammonia to nitrogen in the mixed processing gas is 1:4.
[0071] In the primary irradiation treatment, in a mixed treatment gas environment, the beam current was controlled to be 2.1 mA, the irradiation temperature was 40° C., and the irradiation treatment was performed for 15 minutes to complete the primary irradiation treatment.
[0072] In the secondary irradiation treatment, in the mixed treatment gas environment, the beam current was adjusted to 6 mA and the irradiation temperature was 60°C. After irradiation treatment for 30 minutes, the introduction of the mixed treatment gas was stopped, and the mixed treatment gas in the electron beam constant temperature irradiation device was completely replaced by inert gas (argon), and then kept at 60°C for 10 minutes to complete the secondary irradiation treatment.
[0073] In the three-level irradiation treatment, in an inert gas (argon) environment, the beam current was adjusted to 10 mA, the irradiation temperature was 100°C, and the irradiation treatment was carried out for 25 minutes to complete the three-level irradiation treatment.
[0074] In the fourth-level irradiation treatment, in an inert gas (argon) environment, the beam current is adjusted to 13 mA, the irradiation temperature is 150°C, the irradiation treatment is carried out for 15 minutes, and the irradiation is stopped to complete the fourth-level irradiation treatment.
[0075] 3. Post-processing
[0076] The multi-stage composite treated fibers were transferred into a heating furnace, heated to 280°C, and subjected to annealing treatment for 40 minutes to obtain infusible fibers.
[0077] After testing, the infusible fiber obtained by the infusible treatment method of this embodiment has an infusibility temperature of not less than 500°C, and the fiber surface is smooth and dense, and no melting and twisting occurs (such as Figure 1 The weight loss rate at 1000℃ in nitrogen environment is 17.2% (as shown in Figure 2 As shown); the gel content of the infusible fiber is 98.3%. Furthermore, in the infusible treatment method of this embodiment, the infusible treatment (i.e., multi-stage composite treatment) takes about 1.5 hours, which can improve the infusible treatment efficiency while taking into account the infusible treatment efficiency and infusible treatment effect, and realize the high degree and uniform infusibility of low softening point boron nitride-based fibrils in batches.
[0078] Furthermore, in order to verify the treatment effect of the aforementioned infusible treatment method of this embodiment on boron nitride-based fibers, the infusible fibers obtained by the infusible treatment method of this embodiment were placed in a nitrogen atmosphere, and the heating rate was controlled to be 3°C / min. The temperature was raised to 1000°C and kept warm for 3 hours. Then, in a nitrogen atmosphere, the heating rate was controlled to be 5°C / min, and the temperature was continued to be raised to 1500°C. The temperature was kept warm for 1 hour to obtain silicon-doped boron nitrogen fibers.
[0079] After testing, the final silicon-doped boron nitrogen fiber has a smooth surface, no foreign element dissolution pore defects, a tensile strength of 1.22GPa, and an elastic modulus of 101GPa. After the silicon-doped boron nitrogen fiber was placed in 100°C boiling water for 3 hours, the tensile strength retention rate was 98.7%; after the silicon-doped boron nitrogen fiber was placed in an oxygen-nitrogen mixed gas environment (the volume ratio of oxygen to nitrogen was 3:97) and heat-treated at 1400°C for 30 minutes, the tensile strength retention rate was 95.3%.
[0080] Comparative Example 1
[0081] The batch infusible treatment method of silicon-doped boron-nitrogen precursor fibers of Comparative Example 1 is specifically as follows:
[0082] 1. Melt spinning
[0083] The melt spinning steps of Comparative Example 1 are the same as those of Example 1.
[0084] 2. Multi-stage irradiation treatment
[0085] Under the protection of inert gas (nitrogen), the BN-based fibrils obtained in the melt spinning step are placed in an electron beam constant temperature irradiation device. After the air in the electron beam constant temperature irradiation device is completely replaced by nitrogen, the irradiation energy is controlled to 2.2MeV, and the first-level irradiation treatment, the second-level irradiation treatment, the third-level irradiation treatment, and the fourth-level irradiation treatment are continuously performed to obtain multi-stage irradiation treated fibers.
[0086] Among them, in the first-level irradiation treatment, the beam current is 2.2mA, the irradiation temperature is 34°C, and the irradiation treatment is carried out for 20 minutes.
[0087] In the secondary irradiation treatment, the beam current was adjusted to 4.6 mA, the irradiation temperature was 50° C., and after irradiation treatment for 20 minutes, the irradiation was stopped and kept at 50° C. for 25 minutes to complete the secondary irradiation treatment.
[0088] In the third-level irradiation treatment, the beam current is 9.8 mA, the irradiation temperature is 98°C, and the irradiation treatment is carried out for 20 minutes.
[0089] In the four-level irradiation treatment, the beam current is 14 mA, the irradiation temperature is 160° C., the irradiation treatment is performed for 12 minutes, and the irradiation is stopped to complete the four-level irradiation treatment.
[0090] 3. Post-processing
[0091] The multi-stage irradiation treated fibers were transferred to a heating furnace, heated to 300°C, and annealed for 40 minutes to obtain infusible fibers.
[0092] After testing, the weight loss rate of the infusible fiber prepared in this comparative example at 1000°C in a nitrogen environment was 11.5% (e.g. Figure 2 As shown); the carbon content after heat treatment at 1000℃ in an ammonia environment is 6.8wt% and the color is black.
[0093] In the infusible treatment method of comparative example 1, electron beam irradiation treatment is carried out under the protection of pure inert gas in the multi-stage treatment, and no active gas (ammonia) is added. Although the infusible fiber prepared in comparative example 1 has a lower thermal weight loss, it achieves a certain carbon fixation effect in the multi-stage irradiation process. In the post-treatment process, non-target element carbon (content is 6.8wt%) exists and cannot be effectively removed; it not only directly leads to the presence of impurities in the boron nitride-based fiber prepared by using the infusible fiber, but also directly leads to the reduction of mechanical properties and wave transmission properties of the boron nitride-based fiber.
[0094] Comparative Example 2
[0095] The batch infusible treatment method of silicon-doped boron-nitrogen precursor fibers of Comparative Example 2 is specifically as follows:
[0096] 1. Melt spinning
[0097] The melt spinning steps of Comparative Example 1 are the same as those of Example 1.
[0098] 2. Thermal cross-linking infusible materials
[0099] Under the protection of inert gas (nitrogen), the BN-based raw fibers obtained in the melt spinning step were placed in a heat treatment furnace, ammonia was introduced and the temperature was raised to 300°C, and ammonia heat crosslinking and infusibility treatment was performed for 2 hours to obtain infusible fibers (such as Figure 3 as shown).
[0100] It can be seen that the infusible fiber obtained by the heat-crosslinking infusible treatment method of Comparative Example 2 has a hollow structure, which is not conducive to the subsequent preparation of boron nitride-based fibers and has a great influence on the mechanical properties and wave transmission properties of the boron nitride-based fibers.
[0101] Meanwhile, the weight loss rate of the infusible fiber prepared in this comparative example at 1000°C in a nitrogen environment is 44.2% (e.g. Figure 2 As shown); compared with the infusibility treatment method of the present invention, the infusible fiber prepared in Example 1 has higher thermal stability and a higher degree of infusibility, and the heat treatment efficiency of the infusible fiber in the subsequent preparation of boron nitride-based fibers is higher.
[0102] Unless otherwise specified, all percentages used in the present invention are by mass.
[0103] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A batch infusible treatment method for silicon-doped boron-nitrogen precursor fibers, characterized in that: The method comprises the following steps: melt spinning, multi-stage composite treatment, and post-treatment; The melt spinning method comprises the following steps: using polysilicon borazane as an organic precursor raw material for melt spinning to obtain BN-based fibrils; The multi-stage composite treatment method comprises placing the BN-based original fiber in an electron beam constant temperature irradiation device under the protection of an inert gas, replacing the inert gas in the electron beam constant temperature irradiation device with a mixed treatment gas, continuously introducing the mixed treatment gas into the electron beam constant temperature irradiation device, controlling the irradiation energy to be 2-2.5 MeV, and continuously performing a primary irradiation treatment, a secondary irradiation treatment, a tertiary irradiation treatment, and a quaternary irradiation treatment to obtain a multi-stage composite treated fiber; The mixed treatment gas is a mixed gas of ammonia and nitrogen; the introduction rate of the mixed treatment gas is 3-6m 3 / h; The volume ratio of ammonia to nitrogen in the mixed process gas is 1:2-5; the flow ratio of ammonia to nitrogen in the mixed process gas is 1:2-5; The beam current of the first-stage irradiation treatment is 1.8-2.4 mA, the irradiation temperature is 20-40° C., and the irradiation treatment time is 10-30 min; In the secondary irradiation treatment, a beam current of 4-6 mA and an irradiation temperature of 45-60° C. are first used. After irradiation treatment for 5-30 minutes, the introduction of the mixed treatment gas is stopped, and the mixed treatment gas in the electron beam constant temperature irradiation device is completely replaced by an inert gas. After the mixed treatment gas is kept at 45-60° C., the secondary irradiation treatment is completed. The three-stage irradiation treatment is carried out in an inert gas environment with a controlled beam current of 8-10 mA, an irradiation temperature of 65-110° C., and an irradiation treatment time of 5-25 min. The four-stage irradiation treatment is carried out in an inert gas environment with a controlled beam current of 12-14 mA, an irradiation temperature of 120-160° C., and an irradiation treatment time of 5-15 min. The post-treatment method is to perform annealing treatment on the multi-stage composite treated fibers to obtain infusible fibers.
2. The batch infusibility treatment method of silicon-doped boron-nitrogen precursor fibers according to claim 1, characterized in that: In the melt spinning, the melt spinning diameter is 12-15 μm; The spinning viscosity of polysilicon borazane is 250-850 Pa·s, the molecular weight is 550-1500, and the silicon content accounts for 5-20wt%.
3. The batch infusibility treatment method of silicon-doped boron-nitrogen precursor fibers according to claim 1, characterized in that: In the post-treatment, the annealing temperature is 280-300° C., and the annealing time is 20-60 min.
Citation Information
Patent Citations
Auxiliary gas-phase cross-linking method of electron beams
CN106637915A
Polycarbosilane fiber electron beam irradiation non-melting under-beam device and method
CN111519423A